FEEDING PATTERN TOWARD THE INCREASING OF NUTRITIONAL STATUS IN CHILDREN AGED 1–3 YEARS - Toni Subarkah; Nursalam Nursalam; Praba Diyan Rachmawati (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2016)
Introduction: The prevalence of nutritional status problems with underweight in Indonesia at the moments is (19,6%). Data showed that children with less nutritional status aged 1-3 years in Kalijudan, Surabaya are existed. Provide feeding pattern properly is one effort to improve the nutritional status by fulfilling the needs of the child nutrition. The purpose of this study was to explain the relationship of feeding pattern and nutritional status in children aged 1-3 years in the Kalijudan district, Surabaya. Methods: The research design used was cross-sectional study with dietary habit as the independent variable and nutritional status as dependent variable. The sample was taken from 154 mothers and children. Consecutive sampling was deployed. Data collection by questionnaires, and then data analysis using the Spearman’s Rho in level of significance α≤0.05. Result and Analysis: There was strong relationship between feeding pattern and nutritional status (r=0.640). The result showed that inappropriate feeding patterns with nutritional status is very thin (44.4%) a proper feeding patterns with normal nutritional status (89.7%). Discussion and Conclussion: The efforts to improve nutritional status of children aged 1-3 years related to feeding patterns should be improved in order to achieve a normal nutritional status. Further research may explore on the feeding patterns based on dietary allowances.Keywords: feeding pattern, nutritional status, 1-3 years old children